Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Connect with a community of experts ready to provide precise solutions to your questions quickly and accurately. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Evaluate the expression when [tex]\( x = 20 \)[/tex] and [tex]\( y = -3 \)[/tex].

[tex]\[ 3x + 2y + 2x \][/tex]


Sagot :

To evaluate the expression [tex]\(3x + 2y + 2x\)[/tex] when [tex]\(x = 20\)[/tex] and [tex]\(y = -3\)[/tex], follow these steps:

1. Substitute the values of [tex]\(x\)[/tex] and [tex]\(y\)[/tex] into the expression:
[tex]\[ 3(20) + 2(-3) + 2(20) \][/tex]

2. Calculate each term separately:
- For the term [tex]\(3x\)[/tex]:
[tex]\[ 3 \times 20 = 60 \][/tex]
- For the term [tex]\(2y\)[/tex]:
[tex]\[ 2 \times (-3) = -6 \][/tex]
- For the term [tex]\(2x\)[/tex]:
[tex]\[ 2 \times 20 = 40 \][/tex]

3. Combine the results:
[tex]\[ 60 + (-6) + 40 \][/tex]

4. Add the results step-by-step:
- First, add [tex]\(60\)[/tex] and [tex]\(-6\)[/tex]:
[tex]\[ 60 - 6 = 54 \][/tex]
- Then, add the result to [tex]\(40\)[/tex]:
[tex]\[ 54 + 40 = 94 \][/tex]

So, the value of the expression [tex]\(3x + 2y + 2x\)[/tex] when [tex]\(x = 20\)[/tex] and [tex]\(y = -3\)[/tex] is [tex]\(\boxed{94}\)[/tex].